Language of Diplomacy in Palestinian Discourse: Analysis of Illocutionary Speech Acts in the Speech of The Deputy Minister of Foreign Affairs of Indonesia - Muhammad Farhan Palowa; Muassomah Muassomah; Ma'rifah Munjiah (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
This study aims to identify and analyze the types of illocutionary speech acts used in the speech delivered by Indonesia's Deputy Minister of Foreign Affairs, Anis Matta, at the Preparatory Meeting of the Extraordinary Summit of the Organization of Islamic Cooperation (OIC) and the Arab League, held in Riyadh, Saudi Arabia, on November 10, 2024. The study employs a pragmatic approach based on John Searle’s theory of speech acts. This speech is fascinating to examine due to its use of Arabic in an international forum and its emphasis on the strategic issue of Palestine. The research method employed is a descriptive qualitative approach, utilizing observation and note-taking techniques for data collection. The research findings reveal five types of illocutionary acts based on Searle’s classification: 4 assertive acts in the form of complaints, conclusions, and affirmations; 6 directive acts in the form of invitations, questions, and prayers; 1 commissive act expressing commitment or intention; 2 expressive acts in the form of gratitude and empathy; and two declarative acts that aim to change political status. These illocutionary acts express political convictions, call for collective action, reaffirm Indonesia’s commitment, foster solidarity, and challenge international structures. In the context of global diplomacy, they function as strategic tools to shape narratives, influence opinion, and strengthen Indonesia’s role in supporting Palestine.